THE BUILDING AN ADAPTIVE CAPABILITY MODEL OF HUMAN RESOURCES IN THE DIGITAL TRANSFORMATION OF THE FOOD SUPPLY CHAIN: A PHENOMENOLOGICAL STUDY ON THE PARTNER ECOSYSTEM OF THE NATIONAL NUTRITION AGENCY - Denny Aditya Dwiwarman; Ira Mariah Ulfah; Mohammad Sigit Adi Nugraha; Wenny Djuarni (Amal Insani Foundation, 2026)
This research aims to develop the Generative Adaptive Micro-Foundations Model (GAMF) to explain the generative mechanism for the formation of human resource (HR) adaptive capabilities in the digital transformation of the food supply chain in the ecosystem of the National Nutrition Agency (BGN) Partners. The background of the research was driven by the mass poisoning incident of the Free Nutritious Meal Program in Cianjur Regency in 2025, which revealed the weak competence of human resources, the fragility of the cold chain system, and the reliance on manual monitoring. Previous studies tend to emphasize technological and organizational aspects at the macro level, while the HR adaptation process at the micro level is still a black box. This study uses a qualitative approach of Interpretative Phenomenological Analysis (IPA) by involving 15–20 key actors through in-depth interviews, participatory observation, and document analysis. The results of the analysis identified four main generative mechanisms, namely collective trauma sensemaking, cross-border communities of practice, iterative experimentation cycles, and reflective digital identity construction. These four mechanisms form the adaptive capabilities of HR that enable organizations to navigate the paradox between operational efficiency and food safety. Theoretically, this study advances the study of microfoundations of dynamic capabilities. Practically, the research findings provide the basis for the development of HR policies, adaptive KPI systems, and trauma-based training in the context of food digital transformation.